Cognitive theraphy in a nutshell Michael Neenan and Windy Dryden. - Neenan, Michael (Counselling in a nutshell series, 2011)
Provides a concise, accessible introduction to the key elements of the theory and practice of CBT for absolute beginners. For anyone who wants a clear, focused introduction to the complexities of CBT, this book can be used as a springboard to more in-depth material